Software-Defined Networks as a Stage of the Network Technology Evolution - A. A. Krasotin; I. V. Alexseev (Моделирование и анализ информационных систем, 2013)
The authors of the article focus on the concept of a software defined network. In the beginning, the brief historical account is given concerning software defined networks as a scientific concept, its formation and technological and scientific meaning. The software defined network concept is treated in the article not as the final state-of-the-art in networking, but rather as a possible step and direction in the development of a networking paradigm. The article touches on pros and cons as well of the software defined networking and gives an account of possible stages of development of this technology in the context of other technologies, considering its hybrid with MPLS, as an example. OpenFlow protocol constitutes the main part of the article. The authors further discuss various kinds of existing libraries realizing programmable management routines for a software defined network using OpenFlow. All of these libraries provide API for building modular applications for software defined network management. Touching on practical side of implementation the results of comparative tests of throughput and latency, achieved with these libraries are shown.